1996
DOI: 10.1109/59.544677
|View full text |Cite
|
Sign up to set email alerts
|

Transient stability assessment in longitudinal power systems using artificial neural networks

Abstract: Results of the application of Artificial Neural Networks to the problem of Transient Stability Assessment are presented. This technique is applied to a real Longitudinal Power System that includes discrete supplementary controls. Different representations of the training space patterns and neural networks architectures are investigated. Input variables include topological changes, load and generation levels and contingencies. A special organization of training patterns with a separation by type of contingency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The concept of individual energy function characterizes the transient stability as a local phenomenon in contrast to the total energy function.In [6], 1916 composite indices were generated and performing correlations, 18 composite indices were selected as inputs. In [7], 12 steady state variables were used as inputs and it was reported that dynamic variables did not. improve the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of individual energy function characterizes the transient stability as a local phenomenon in contrast to the total energy function.In [6], 1916 composite indices were generated and performing correlations, 18 composite indices were selected as inputs. In [7], 12 steady state variables were used as inputs and it was reported that dynamic variables did not. improve the results.…”
Section: Discussionmentioning
confidence: 99%
“…Faults at mar?y locations have to be considered to evaluate the capability of ANN. In [7], training patterns were divided into many sets and separate ANN was used to predict stability for each set. Classification errors of less than 1% for training set and less than 5% for test set were obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) the model parameter selection is difficult and training results are not stable. To solve the above problems, this paper uses support vector machine developed from statistical learning theory to build a new transient stability assessment model [1]. The proposed model contains bagging and approximate reasoning strategy, which can make accurate reasoning for the unknown sample and improves the stability and accuracy of the prediction.…”
Section: Introductionmentioning
confidence: 99%
“…But these methods practical applications still exist some problems, mainly as follows: (1) The generalization error of transient stability assessment can not be guaranteed. (2) the model parameter selection is difficult and training results are not stable.…”
Section: Introductionmentioning
confidence: 99%